Upper airway obstruction secondary to laryngeal epidermoid cyst in cat: Case report - da Silva, Bruno Ricardo Soares Alberigi; Filho, Mário dos Santos; Soares, Denise do vale; Mattos, Rebeca Guimaraes Moraes Rego Bhering; e Suzano, Sara Maria de Carvalho; Paiva, Jonimar Pereira (Brazilian Journal of Veterinary Medicine, 2018)
Laryngeal diseases are rare in cats, but when present they can cause significant dyspnea, compromising the ideal supply of oxygen to the body. A female cat, of 15 years old, mixed breed, was attended in dyspnea state. With findings of physical examination and complementary exams cervical neoplasia was suspected to obstruct the upper airways. After the histopathological analysis of the mass found in the region of the larynx, it was concluded that it was a benign mass that compromised the flow of air through the larynx. The present work aims to report a case of a laryngeal epidermoid cyst causing upper airway obstruction in a cat, describing its physical examination findings and imaging as diagnostic support.